Avaliação do uso de nanofirbas incorporadas com óleo ozonizado na cicatrização da exodontia de terceiros molares inferiores: ensaio clínico randomizado, boca dividida, prospectivo, duplo cego - Machado, Brenda Rex (2025)
Electrospun nanofibers have been developed with the aim of accelerating healing. These absorbable membranes act to fix the clot and stabilize the wound. To enhance these benefits, ozonated oil has emerged as an option with high antioxidant power. Therefore, the aim of this randomized, split-mouth, prospective, double-blind clinical trial was to verify the effect of using a membrane loaded with ozonated oil on the healing process in lower third molar extractions when compared to the conventional technique. The study followed the CONSORT declaration, was registered with ReBEC and approved by the Local Ethics Committee. Patients with an indication for extraction of semi-retained lower third molars were selected. The fiber was obtained from Ecovio® solutions and a solution was prepared without additives; one with sunflower oil and one with ozonated sunflower oil. The sample of 36 patients totaled 72 teeth and was divided into 4 approach groups for the operated teeth (Negative Control, White Control 1, White Control 2 and Treatment), which were randomized into 6 groups with 6 patients each. The healing of each patient was assessed 64 days after surgery. The data collected was evaluated using descriptive statistics and compared between the groups using Generalized Linear Mixed Models and the Tukey-NHSD post-test. It was concluded that the groups had similar final behaviors, with white control 1 showing the highest mean percentage of initial gingival healing and white control 2 the highest mean percentage of initial bone repair.